Radical abdominal trachelectomy and pelvic lymphadenectomy in a nulliparous patient with cervical adenocarcinoma: A case report - Elpis Galati; Victoria Psomiadou; Fotios Lefkopoulos; Athanasios Douligeris; Anastasia Prodromidou; Evgenia Karavioti; Christos Iavazzo; Alexandros Rodolakis; George Vorgias (Elsevier, 2019)
Cancer of the cervix is the fourth most common malignancy among women in the world and the sixth most common among women in Europe. Almost half of patients with an early-stage invasive cervical carcinoma are under 40 years of age, while the average age at first pregnancy in European countries is over 28 years. Therefore many women with cervical cancer have not started or completed their family at the time of diagnosis and ask for fertility-sparing surgery. Radical trachelectomy is a safe alternative to standard care (radical hysterectomy) for patients diagnosed with early-stage cervical cancer and is a reasonable choice in well selected cases. We present the case of a 23-year-old patient diagnosed with a cervical adenocarcinoma and treated with abdominal trachelectomy. Keywords: Cervical cancer, Adenocarcinoma, Radical trachelectomy, Nulliparous patient